2004
DOI: 10.1364/josaa.21.001761
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the scattering properties of coupled metallic nanoparticles

Abstract: We apply the boundary element method to the analysis of the plasmon response of systems that consist of coupled metallic nanoscatterers. For systems made of two or more objects, the response depends strongly on the individual particle behavior as well as on the separation distance and on the configuration of the particles relative to the illumination direction. By analyzing the behavior of these systems, we determine the smallest interaction distance at which the particles can be considered decoupled. We discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 21 publications
1
27
0
1
Order By: Relevance
“…2a, when the gap distance g increases, the SCS peaks in visible light region show blue-shifted, and the intensity of SCS decreases as the gap distance increases. The intensity of SCS for two particle pairs is much larger than that obtained from single particles (multiplied by a factor of two [31]). A very different behavior is observed for the other polarization direction, as illustrated in Fig.…”
Section: Simulation Models and Resultsmentioning
confidence: 75%
“…2a, when the gap distance g increases, the SCS peaks in visible light region show blue-shifted, and the intensity of SCS decreases as the gap distance increases. The intensity of SCS for two particle pairs is much larger than that obtained from single particles (multiplied by a factor of two [31]). A very different behavior is observed for the other polarization direction, as illustrated in Fig.…”
Section: Simulation Models and Resultsmentioning
confidence: 75%
“…The cylinder is illuminated with a TM polarized plane wave (electric field parallel to the cylinder axis) that propagates parallel to the short axis. Simulations were done with the boundary element method [41,42]. It can be observed that with increasing axis ratio the resonance, which is associated with the electron oscillation along the major axis, shifts to larger wavelengths and increases in width.…”
Section: Tuning the Spectral Positions Of Localized Plasmon Polaritonsmentioning
confidence: 99%
“…In plasmonics [1,2,3], subwavelength metal structures are used to confine and enhance [4,5], guide [6,7], and scatter [8,9,10,11] light. The goal to measure and control light at ever smaller length scales drives the research field towards true nanoplasmonics.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical grid size ∆x must be smaller than all physical length scales in our study, and the latter satisfy k −1 F < L ≪ λ . The core of this article is a numerical study of nonlocal-response effects when light scatters off nanoplasmonic dimer structures, which are archetypical structures to study both field enhancement [4,18], scattering [8,9], and hybridization of plasmonic resonances [19,20,21,22]. Important is also that dimers can display resonances in the visible [23] even when their two constituents, taken separately, would not.…”
Section: Introductionmentioning
confidence: 99%